POSTĘPOWANIE W SPRAWACH O CRIMEN MAIESTATIS W OKRESIE REPUBLIKI RZYMSKIEJ - Dyjakowska, Marzena Hanna (Zeszyty Prawnicze, 2017)
Procedural Issues of the crimen maiestatis in Roman Republic Summary The article presents some procedural issues of crimen maiestatis in the Roman Republic. The first approach examines the process by which the public criminal law evolved rules for the protection of maiestas populi Romani, and the application o f these rules in particular cases. This topic is introduced by analysing the concept of maiestas with a particular reference to maiestas populi Romani. The crimen maiestatis was first brought within the ambit of the public criminal law by way of the fragmentation of a particular segment o f a diffuse crime of perduellio. The role of the duoviri perduellionis, as well the origin and nature o f the criminal jurisdiction of the tribuni and aedilesalso are to be discussed. The duoviri are recorded only three times: first there is the Livy’s account of the famous trial of Horatius under King Tullus Hostilius. It is also discussed in the article when and how provocatio against the higher fines was introduced. In the Roman Republic the maiestas cases were tried before the plebs or the comitia centuriata of the people. The lex Appuleia maiestatis established a permanent quaestio maiestatis and brought a particular category of wrongful acts under its jurisdiction. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />